Psychological mechanisms underlying the relationship between commercial physical activity app use and physical activity engagement. (November 2020) - Petersen, Jasmine M.; Kemps, Eva; Lewis, Lucy K.; Prichard, Ivanka
Abstract: Purpose: Previous studies have indicated a relationship between the use of commercial physical activity apps (e.g., Fitbit, Strava) and physical activity engagement. The use of social components of such apps, in particular app-specific communities (connecting with other app users) and existing social networking platforms (e.g., Facebook) have the potential to enhance physical activity. This study aimed to explore the psychological mechanisms underlying the relationship between the use of commercial physical activity apps (and their social components) and physical activity engagement. Method: An online cross-sectional survey assessed physical activity, use of commercial physical activity apps (and their associated social components), and psychological constructs (social support, self-efficacy, motivation, trait competitiveness, trait social comparison). Results: 1274 adults aged 18–83 years (Mage  = 34.1 ± 13.5 years, 87.6% female) participated. App use was positively associated with physical activity engagement. The relationship between app use and physical activity was fully mediated by social support, self-efficacy, intrinsic motivation and identified regulation. Trait competitiveness, but not trait social comparison, moderated the relationship between app use and physical activity. Most features (e.g., sharing posts, providing or receiving encouragement) of the social components of apps were positively associated with psychological constructs linked to engagement in physical activity. Mediation pathways linking features of existing social networking platforms with physical activity were found. Specifically, sharing posts was linked to higher engagement in physical activity via positive associations with self-efficacy, and receiving encouragement with linked to higher engagement in physical activity via positive associations with both self-efficacy and identified regulation. In addition, engagement in comparisons was associated with lower self-efficacy and higher external regulation, and in turn, lower physical activity. Conclusions: The relationship between the use of commercial physical activity apps and physical activity is underpinned by social support, self-efficacy and autonomous motivations. The findings highlight the importance of trait competitiveness, which should be taken into consideration when leveraging physical activity apps. Overall, the present study demonstrated that commercial physical activity apps (and their social components) hold great potential to increase physical activity engagement given their associations with psychological constructs strongly linked with physical activity. Highlights: Commercial physical activity apps and their social components are associated with greater engagement in physical activity. Social support, self-efficacy and autonomous motivations mediated the relationship between app use and physical activity. Trait competitiveness moderated the relationship between app use and physical activity.